UTILITY AND SIGNIFICANCE OF NATIONAL LANGUAGE URDU AS MEDIUM OF INSTRUCTION IN EDUCATION OF PAKISTAN - Asia Khatoon; Ann Samson; Safia Niazi; Abdul jabbar Dahri (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The discussion of the vehicle of guidance in Pakistan is old and its foundations date back to the pre-Freedom Frontier period. Pakistan acquired an instructive construction from the English Domain which was later generally changed yet its specific fundamental highlights are set up to date. The expulsion of Urduand, in its stead, the consideration of English as a vehicle of guidance is one such component which, by its own doing, is a very much perceived pilgrim relic. The utilization of English as a vehicle of guidance in Pakistan has its protectors just as doubters. Notwithstanding, what is urgently absent in this discussion, is the well-qualified assessment and the proof based specialized and impartial investigation of the current issue. Countless individuals who as a rule take part in this discussion will in general concoct unconfirmed cases and assessment based speculations. This paper plans to make a very much validated examination of the misfortune and gain of the mechanism of guidance, andexamines the pertinence and worth of the main language (for our situation, Urdu)in the setting of the mode of guidance. At long last, the paper hopes to achieve an educated arrangement regarding the interaction, setting, goals, and results of the mechanism of guidance from the viewpoint of language teaching method and arranging.